Dante e fumetti: Ricadute nella didattica, suggestioni divulgative (Itinera, 2023)
Dante’s Divina Commedia is one of the most influential literary works in Italy and not only. Reading, understanding and analysing it are a fundamental part of the skills every Italian student should reach, due to the national school programs, particularly in middle and high school. Many Italians and internationals comics’authors worked on Divina Commedia, feeding the collective imagination about Dante, giving new readings of popular suggestions – in this paper, we’ll partially analyse Marcello Toninelli’s and GōNagai’s works, as influences in didactics, but also as peculiar products, with a universal approach, inspired by Dante’s world. So comics can also be considered didactic media. In fact students can be involved in a process where they could build their own comics based on Divina Commedia. Considering both Divina Commedia and comics linguistic media, every student will be able to join a travel from literature to comics and back, creating a final original product, testifying comprehension and personalization of the original literary work.
Keywords: Divina Commedia, didactic use of comics, Marcello Toninelli, GōNagai.